1996
DOI: 10.1101/gr.6.5.414
|View full text |Cite
|
Sign up to set email alerts
|

A P1-based physical map of the Drosophila euchromatic genome.

Abstract: A PCR-based sequence-tagged site (STS) content mapping strategy has been used to generate a physical map with 90% coverage of the 120-Mb euchromatic portion of the Drosophila genome. To facilitate map completion, the bulk of the STS markers was chosen in a nonrandom fashion. To ensure that all contigs were localized in relation to each other and the genome, these contig-building procedures were performed in conjunction with a large-scale in situ hybridization analysis of randomly selected clones from a Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 35 publications
0
41
0
1
Order By: Relevance
“…To isolate the entire gene, we used the 2-90 cDNA insert to probe a macroarray of D. melanogaster genomic P1 clones; we found two (overlapping) P1 clones that hybridized to 2-90 cDNA. These clones, DS00857 and DS00968, previously had been mapped to a contig containing tra2 (28). Restriction maps of the smaller (DS00857) suggested that the HP2 gene was located near the P element insertion site l(2)07214.…”
Section: Resultsmentioning
confidence: 99%
“…To isolate the entire gene, we used the 2-90 cDNA insert to probe a macroarray of D. melanogaster genomic P1 clones; we found two (overlapping) P1 clones that hybridized to 2-90 cDNA. These clones, DS00857 and DS00968, previously had been mapped to a contig containing tra2 (28). Restriction maps of the smaller (DS00857) suggested that the HP2 gene was located near the P element insertion site l(2)07214.…”
Section: Resultsmentioning
confidence: 99%
“…We used mapped STSs as a source of genomic sequences (Kimmerly et al 1996). At the time this project was initiated, these STSs were the only mapped sequence elements with a genome-wide distribution of the required density.…”
Section: Genome-wide Snp Discoverymentioning
confidence: 99%
“…Using genomic DNA from six wild-type strains (Barcelona, Capetown, Hikone, Pyrenees, w;iso2;iso3, and a P-element containing strain) as templates, we compared sequences from 24 third chromosome sequence tagged sites (STSs) from the P1-based physical map of the genome (Kimmerly et al 1996). The results shown in Table 1 indicate that the rate of sequence variation between any two strains ranges from 2.1 per kilobase (1 polymorphism/476 bp) to 5.2 per kilobase (1 polymorphism/192 bp, Table 1A), in agreement with previous studies.…”
mentioning
confidence: 99%
“…A genomic fragment covering the 2.2-kb upstream region of the D. melanogaster rho gene was generated by PCR using the D. melanogaster genomic P1 clone DS02734 (GenBank accession number AC004343) as a template (Kimmerly et al, 1996), and subcloned into the BamHI site of pCaSpeR-NLSlacZ (gift of C. Thummel, Howard Hughes Medical Institute, University of Utah, Salt Lake City, UT …”
Section: Transgene Construction For Rho Enhancer Analysismentioning
confidence: 99%